Whole-Brain Radiation Therapy With Simultaneous Integrated Boost Versus Whole-Brain Radiation Therapy Plus Stereotactic Radiosurgery for the Treatment of Brain Metastasis From Lung Cancer - Lin, Binwei; Huang, Dan; Du, Huan; Fan, Jinjia; Zhang, Yu; Feng, Gang; Gao, Feng; Du, Xiao Bo (Frontiers in Oncology, 2021)
Radiotherapy is one of the most important treatments for brain metastasis (BM). This study aimed to assess whether whole-brain radiation therapy (WBRT) with simultaneous integrated boost (SIB) provided any therapeutic benefit compared to WBRT followed by stereotactic radiosurgery (SRS). Seventy-two consecutive cases of lung cancer with BM treated from January 2014 to June 2020 were analyzed retrospectively. Thirty-seven patients were treated with WBRT (30 Gy in 10 fractions) and SIB (45 Gy in 10 fractions), and 35 patients were treated with WBRT (30 Gy in ten fractions) followed by SRS (16–24 Gy according to the maximum tumor diameter). The secondary endpoints primary endpoint was intracranial progression-free survival (PFS). The secondary endpoints were intracranial objective response (partial and complete responses), pattern of intracranial progression, overall survival (OS), and toxicity.The WBRT + SIB group had a significantly longer median intracranial PFS (9.1 vs. 5.9 months, P = 0.001) than the WBRT + SRS group. The intracranial objective response rate was 67.6% and 62.9% in the WBRT + SIB and in WBRT + SRS groups, respectively (P = 0.675). The incidence of progression outside the P-GTV in the WBRT + SIB group was significantly lower than that in the WBRT + SRS group (39.4% vs. 75.0%, P = 0.004). The median OS was 24.3 and 20.3 months in the WBRT + SIB and WBRT + SRS groups, respectively (P = 0.205). There was no significant difference in the incidence of grade 3 or worse adverse reactions between the two groups. Compared to treatment with WBRT + SRS, that with WBRT + SIB for BM appeared to contribute to local control.